Chapter Active and Passive Acoustic Methods for In-situ Monitoring of the Ocean Status - Pensieri, Sara (InTechOpen, 2017)
Recent European strategic plans for the successful monitoring of the status of the ocean push on the development of an integrated observing system able to further link existing instruments and techniques with the aim to complement each other and answer open issues. A more intensive use of acoustic devices could contribute to the knowledge of oceanographic processes exploiting the characteristic of sound to travel in the ocean for a wide area than in the atmosphere. In this context, the installation of passive acoustic instruments, able to listen to ambient noise on fixed or mobile platforms, could contribute to provide information on sound budget and to enhance the monitoring capacity of meteorological phenomena also in the open ocean. Instead, the deployment of active acoustic instruments can be of benefit for monitoring biological activities through the analysis of backscatter data as well as for monitoring ocean waves.